Non-right-handedness and asthma - Krommydas, Georgios C.; Gourgoulianis, Konstantinos I.; Raftopoulos, Vasilios (My University, 2004)
This preliminary study aimed to estimate the evolution of asthma from adolescence to adulthood in a subgroup of left-handed and ambidextrous individuals with asthma.
Keywords: Asthma; Adults; Left-handedness